High eyewitness confidence is always compelling: that’s a problem - Key, Kylie N. (Psychology, crime & law, 2023)
Recent research shows a strong positive relationship between eyewitness confidence and identification accuracy, assuming the confidence judgment results from a first, fair test of memory. The current study examines whether jurors understand this relationship, and the boundary conditions under which this understanding holds. Mock jurors read a trial transcript in which we manipulated the eyewitness’ level of confidence (high vs. low), the timing of the confidence judgment (initial, courtroom), and its consistency (if the eyewitness expressed initial and courtroom confidence, did the two judgments match). Mock jurors voted guilty more when confidence was high, regardless of when the confidence judgment was made, or whether there were inconsistencies in the confidence levels. Jurors need a more nuanced appreciation of the role of eyewitness confidence, and we discuss ideas for potential interventions that may aid jurors’ decision making.